THE VALIDITY AND PRACTICALITY OF E-BOOK FLIPBOOK-BASED ON TISSUES STRUCTURE AND ORGAN FUNCTION OF PLANT IN 11TH GRADES HIGH SCHOOL MATERIAL - Bella Septiana; Sifak Indana; Ahmad Bashri (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2018)
Flipbook is one of media-based e-Book designed with a software application-shaped book that containing the intended content, such as pages and can be well-thumbed. Media development e-Book with flipbook-based is one of supporting learning in the curriculum of 2013 on Biology material Base Competence of 3.3. Analyzing the relationship between the structure of the cells in tissue of the organ functions in plants and 4.3. Presenting data on observations of the structure of tissues and organs in plants. The purpose of this study was to develop electronic textbook (e-Book) flipbook-based of the material tissue structure and function of plant organs as well as to describe the validity and practicality. The stages of the development e-Book reference to development model ADDIE (Analysis, Design, Development, Implementation or Delivery, and Evaluations). The validity obtained based on the validation expert lecturer material and expert lecturer media. The practicality obtained from readability of e-Book flipbook-based and students' response. The results of the validation media showed the average value based on component of content, component of the presentation, and linguistic component was 4 with the valid criteria. The practicality of e-Book flipbook-based on readability showed that e-Book fit for student in 11th grades and students' response showed the average value was 98.33%. The overall results of the study concluded that e-Book flipbook-based suitable for use as a learning medium in supporting learning tissue structure and function of plant organs material for eleventh high school students. Keywords: E-Book flipbook-based, development, tissue structure and organs function of plant